FRI0461 Efficacy and safety of antifibrotic agents in idiopathic pulmonary fibrosis. (12th June 2018) - Nuñez-García, L.; Valenzuela, C.; Alonso, T.; Vicente, E.F.; Ancochea, J.; Castañeda, S.
Abstract : Background: Antifibrotic (AF) agents are a family of drugs that improve the survival and quality of life of patients with idiopathic pulmonary fibrosis (IPF). Given that pulmonary fibrosis is also a common manifestation of many autoimmune diseases, we think of interest to know the efficacy and safety data of these agents in real life, which will likely soon reach the therapeutic arsenal of the rheumatologist. Objectives: To analyse the efficacy and safety of treatment with AF pirfenidone (Pi) and nintedanib (Ni) at one year in patients with mild-moderate IPF treated in our hospital according to clinical practice. Methods: Retrospective observational study in which all patients diagnosed with mild-moderate IPF who started treatment with Pi and/or Ni between January 2012 and May 2017 in our Hospital were included. The response was evaluated according to the results obtained in the Respiratory Function Tests: forced vital capacity (FVC) and carbon monoxide diffusion test (DLCO), which were carried out every 3 months during the first year of treatment. Some of the patients received both drugs in different evolutionary periods of their disease. The study was approved by the Clinical Research Ethics Committee (CREC) of our hospital. Results: Of the 42 patients included, 29 received Pi, 69% men and 31% women, with a mean age of 71 years (78% ex-smokers). Baseline FVC was 2140 ml (74.4% of the predicted value) and DLCO was 40.8% with respect to the expected value. The absolute loss in FVC after 52 weeks of follow-up was 200 ml. 48.3% required treatment with glucocorticoids (GC) at some point, either due to exacerbations of the disease or as concomitant treatment. 65.5% presented some adverse reaction to Pi, being gastrointestinal discomfort (GI) the most frequently observed, although mainly of self-limiting course, with the definitive suspension of the drug being necessary in 6 cases. As for the patients treated with Ni, 70.6% were men and 29.4% women, 82% ex-smokers, with an average age of 72 years. Baseline CVF value was 2480 ml (83.8% of the predicted value) and DLCO value was 54.7%. The decrease in FVC in absolute terms was 70 ml. Similarly, 4 patients required the use of GC at some point in the study. With regard to adverse reactions, 76.5% presented some type of adverse event, GI discomfort being the most frequent, followed by increased transaminases and mild diarrhoea. The great majority were of limited duration, requiring the definitive suspension of the drug in 5 patients. Five patients treated with Pi died due to exacerbations of their disease. Conclusions: This project supports, with data from usual clinical practice, the beneficial effect of the AF drugs available for the treatment of mild-moderate IPF. Both drugs have been shown to slow down the natural evolution of the disease, reducing the loss of FVC, a variable directly related to mortality. This therapy has acceptable safety margins. However, there are still no references regarding its administration in incipient and advanced stages of the disease nor on their combined use with each other or with immunomodulators for the control of immune mediated diseases. Acknowledgements: To the nurses and all members of the Pneumology Service for their collaboration in the follow-up of the patients included in this study. Disclosure of Interest: None declared